A functional mesoporous ionic crystal based on polyoxometalate. Issue 7 (25th January 2016) - Kawahara, Ryosuke; Niinomi, Kazuma; Kondo, Junko N.; Hibino, Mitsuhiro; Mizuno, Noritaka; Uchida, Sayaka
Abstract : A mesoporous ionic crystal is synthesized with a polyoxometalate and a macrocation with polar cyano groups. The compound possesses one-dimensional mesopores and shows high proton conductivity and catalytic activity, which are due to the water molecules in the mesopores. Abstract : A mesoporous ionic crystal is synthesized with a polyoxometalate and a macrocation with polar cyano groups. The compound possesses one-dimensional mesopores with an opening of 3.0 × 2.0 nm. The compound shows high proton conductivity and catalytic activity, which are due to the water molecules in the mesopores.